Optimization Of Video Media Education About Prevention Bullying In Mothers With Children - Siti Mardiyah; Nurul Devi Ardiani (IJCS: International Journal of Community Service, 2023)
Abstract: Unfavorable behavior that is carried out individually or in groups towards other individuals or groups that is carried out continuously or continuously, repeatedly by means of physical, psychological or mental harm. These actions can lead to depression, sadness and other bad behavior. Bullying can be minimized by increasing knowledge about bullying prevention with education. Community service locations have been carried out at Posyandu Banyurip Kalikobok Sragen. The output of the activity is being able to increase mother's knowledge about the importance of preventing bullying in children. The implementation has been carried out in January-February 2023 at Posyandu Banyurip Kalikobok Tanon Sragen. The method used is the provision of videos and discussions. The media and tools used are video. The results of the implementation of community service activities, namely that there was a change in increasing knowledge of mothers about bullying prevention, namely from 66.25%, after being given health education increased to 98.125%.